2022
DOI: 10.1002/ejoc.202201103
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of N‐Tosylhydrazones with Tetrazoles: A Regioselective Synthesis of 2,5‐Disubstituted‐2H‐Tetrazoles

Abstract: Herein we describe the CÀ N coupling reaction of N-tosylhydrazones with tetrazoles using thermic activation in the presence of different bases. The reactions proved to be highly regioselective to result in the corresponding 2,5-disubstituted-2H-tetrazoles as main products and 1,5-disubstituted-1H-tetrazoles as minor products. Owing to its mild conditions, the method enabled the use of a wide range of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5] Notably, they have the highest number of nitrogen atoms among the stable N-heterocycles and have been widely considered as a suitable precursor to various important scaffolds. [6][7][8][9][10] Recent studies have shown that there has been renewed interest in the preparation of tetrazoles as a substantial number of active pharmaceutical ingredients (API) contain the tetrazole ring. [11][12][13][14] For instance,numerous pharmacological applications of tetrazoles are anti-inflammatory, antihypertensive, anticancer, antiallergic, antibiotic, diuretics and receptor modulatory agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Notably, they have the highest number of nitrogen atoms among the stable N-heterocycles and have been widely considered as a suitable precursor to various important scaffolds. [6][7][8][9][10] Recent studies have shown that there has been renewed interest in the preparation of tetrazoles as a substantial number of active pharmaceutical ingredients (API) contain the tetrazole ring. [11][12][13][14] For instance,numerous pharmacological applications of tetrazoles are anti-inflammatory, antihypertensive, anticancer, antiallergic, antibiotic, diuretics and receptor modulatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the various nitrogen‐containing heterocycles, scaffolds based on tetrazole offer a plethora of applications in the domain of medicinal chemistry, coordination chemistry, material sciences, high energy materials, biochemistry, pharmacology, and agriculture (as herbicides and fungicides) [1–5] . Notably, they have the highest number of nitrogen atoms among the stable N‐ heterocycle s and have been widely considered as a suitable precursor to various important scaffolds [6–10] . Recent studies have shown that there has been renewed interest in the preparation of tetrazoles as a substantial number of active pharmaceutical ingredients (API) contain the tetrazole ring [11–14] .…”
Section: Introductionmentioning
confidence: 99%